Nonlinear Dynamic Characteristic Analysis of Planetary Gear Transmission System for the Wind Turbine - Ren, Zhao-Hui; Fu, Liang; Liu, Ying-Juan; Zhou, Shi-Hua; Wen, Bang-Chun (Journal of Applied Nonlinear Dynamics, 2026)
Foreign Object Debris (FOD) is debris or article alien, which may A compared with the translational-torsional dynamic model of planetary gear transmission system (PGTS) used in wind turbine is established in order to analyze the dynamic characteristics of the PGTS more accurately. The influences of the meshing stiffness, input and output torques, meshing error, nonlinear characteristics of the support bearing and gravity are considered in the model. Based on previous model, the vibration differential equations of the drive-train are obtained through the Lagrange’s equation. The dynamic response characteristics are investigated using the Runge–Kutta numerical method, and the factors of the above proposed excitation are analyzed. The results show clearly that the vibration responses have different characteristics due to the different speeds of each component in the PGTS. The nonlinear behaviour of support bearing causes the dynamic response more complicated In addition, under the internal and external excitations, more frequency multiplication and frequency combination components appear. The vibration frequency components of the system are mainly concentrated in the frequency range below 200Hz. The results of the study in this paper can provide necessary theoretical basis for natural characteristics study, dynamic response and optimization design method of the MW wind turbine PGTS.